The Slippery Role of Induction Chemotherapy in Head and Neck Cancer: Myth and Reality - Ferrari, Daris; Ghi, Maria Grazia; Franzese, Ciro; Codecà, Carla; Gau, Max; Fayette, Jerome (Frontiers in Oncology, 2020)
Chemoradiotherapy as an alternative to surgery can be offered to patients affected by loco-regionally advanced head and neck cancer. Induction chemotherapy is a valid option, supported by few positive trials, but its real efficacy is still a matter of debate. The standard regimen for induction chemotherapy in Europe is a combination of docetaxel (75 mg/m2) and reduced dose doses of cisplatin (75 mg/m2) and 5-fluorouracil (750 mg/m2 day, for five consecutive days) (TPF). It is less toxic and more efficient than the historical therapy PF (cisplatin 100 mg/m2 and fluorouracil 1000 mg/m2/day for five consecutive days). However, in some studies treatment-related mortality has been reported to be as high as 6%. Therefore, some less toxic combinations, such as a modified TPF regimen and the combination of carboplatin plus paclitaxel have been studied. These regimens are showing promising results but deserve further validation in comparative trials. Furthermore, several trials are underway in order to enhance TPF with immune checkpoints inhibitors. Compared to chemoradiotherapy, induction chemotherapy followed by chemoradiation was shown to be non-inferior, and it could decrease the distant metastatic progression, especially in high-risk populations. For selected patients, induction chemotherapy could be a strong option. The chemoselective process that leads to immediate surgery for non-responders, the high response rate (complete responses are sometimes observed), and the survival data, are all arguments in favor of induction chemotherapy, if performed in experienced centers involving health professionals in the context of a skilled multidisciplinary team.